COMPETENCY DEVELOPMENT OF CENTRAL SERVICE PERSONNEL OF THE BANK OF AYUDHYA PUBLIC COMPANY LIMITER IN BANGKOK - Prommasakha na sakonnakhon, Patanapong (Journal of Buddhist Anthropology, 2021)
The objectives of this research were to 1) study the general condition of central service personnel of Bank of Ayudhya Public Company Limited in Bangkok, 2) study the competency of personnel and the need for the development of central service personnel of Bank of Ayudhya and 3) Create guidelines for the competency development of central service personnel of Bank of Ayudhya. This was a mixed research method, collecting data from 795 central service personnel of Bank of Ayudhya, using Yamane’s calculation principles by using questionnaires and in-depth interviews. And have specialized knowledge and flexibility Work fast, efficient Have a positive attitude towards the organization Be honest, respect bank regulations and have good working morale. The bank has an incentive to perform its duties. Salary adjustments are made. There is a good bonus and if good results will be promoted to study abroad. In addition, there is a policy of not reducing employees and creating incentives for compensation that are appropriate for their duties. If wanting to continue to study at a higher level, scholarships or compensation and professional fees will be awarded in special circumstances. And human resource development needs. Human resource planning is in line with the strategic planning of the central service department. 3) to create guidelines for competency development. of the central service personnel of Bank of Ayudhya has established guidelines for development in welfare Personnel selection Team work Yield management Development and training of personal status, financial management.